Entrepreneurship Education and Green Entrepreneurial Intention: A Religious Perspective as a Moderating Variable - Ali Usman; Kurjono; Heni Mulyani (Jurnal Inovasi Pendidikan Ekonomi, 2025)
This paper aims to investigate the degree to which entrepreneurial education and religiosity affect green entrepreneurial intention and how religiosity moderates. This study used a quantitative method via a survey of 200 prospective teacher students at the Faculty of Economics and Business Education, Universitas Pendidikan Indonesia. The study uses SEM-PLS to evaluate the causal connections among the variables. The results show that students' green entrepreneurship intention is much influenced by entrepreneurial education and religiosity. Furthermore, enhancing this link depends on religion. The main contribution of this study is to show how religiosity affects students with higher levels of religiosity: those with more religiosity show a stronger connection between entrepreneurial education and green entrepreneurial intention. This data underlines the need of a whole approach in promoting sustainable entrepreneurship based on values and ethics. It also provides higher education institutions with practical consequences for creating entrepreneurial courses more inclusive of religious beliefs and sustainability, entrepreneurial programs should not just stress commercial skills but also develop ethical consciousness and social responsibility toward the environment. A fresh element and a new perspective on research on green entrepreneurial intention is added by the use of religiosity as a moderating variable in this study